Idioms in Biblical Hebrew : towards their identification and classification with special reference to 1 and 2 Samuel - Van den Heever, Cornelius Marthinus (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.